That's what frenemies are for : a novel - Littlefield, Sophie; Gershell, Lauren (Ballantine Books, 2019)
"A Manhattan socialite turns her spin instructor into a fitness superstar to impress her friends. But can she keep her little project under control? Or has she created a monster? Julia Summers seems to have it all: a Fifth Avenue apartment, a successful husband, and two adorable children attending the best private school in the city. She relishes wielding influence over her well-heeled girlfriends. but her star appears to be fading. That's why, when stranded in Manhattan for the summer as the entire Upper East Side flees to the Hamptons, Julia is on the hunt for the next big thing--the hot new fad that will put her back on top. Enter Flame, the next elite fitness craze. Seductive and transformative, Flame is exactly what Julia needs--and demure, naïve instructor Tatum is her ticket in. Turning Tatum from giggly blonde to trendy guru proves hard work. Yet Julia's triumphant comeback at summer's end doesn't quite go as planned, and when things suddenly get ugly, she realizes she's in way over her head. And Tatum begins to grasp just how much power her newfound stardom holds. Then, with Julia's life already spiraling out of control, her husband is arrested for fraud and bribery. As her so-called friends turn their backs on her, and Tatum pursues her own agenda, Julia is forced to rethink everything she knew about her world to reclaim her perfect life. But does she even want it back? Hilarious and incisive, Sophie Littlefield and Lauren Gershell's That's What Frenemies Are For provides an engrossing glimpse into the cutthroat moms' club of the Upper East Side"--